The Philippines answers the call: Defining the tax regime of call centers in the PEZA-administered ecozones - Andres, Paraluman D. (Animo Repository, 2008)
The Philippines’ call center industry is one of the fastest-growing industries in the country. The revenues generated by call centers help the government boost the country’s economy. With the growing competition of offshore sites for call centers in the Asia Pacific, the Philippines offers a host of tax incentives to retain investments and attract more investors to locate in the country. The research focuses on the impact of tax incentives on the decision of call centers to set up operations in the Philippines. It will investigate whether these incentives indeed motivate investments in the Philippines. It will also delve into whether existing tax laws and regulations need revisions, amendments, or repeal to address the issue surrounding the tax regime of call centers in the PEZA-administered ecozones.